2023
DOI: 10.1108/ijse-12-2022-0776
|View full text |Cite
|
Sign up to set email alerts
|

Farmer's financial literacy and its determinants: evidence from South Asia

Abstract: PurposeThe objective of this study is to ascertain the financial literacy (FL) of the farmers in three South Asian economies (India, Bangladesh and Pakistan). Further, an effort was made to explore various demographic and socioeconomic antecedents of FL of the farmers.Design/methodology/approachThe study used secondary data of 11,025, 782 and 657 farmers from India, Bangladesh and Pakistan respectively from Financial Inclusion Insights (2017) database. “Big five” FL questions were used to measure the FL of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…A statistically significant correlation was found between farm size and keeping of financial information (both in terms of area and share total area). The findings support the studies carried out in other countries, as cited by Lalrinmawia and Gupta (2015), Sivakumar et al (2013), and Das and Maji (2023). As a result, more focus should be given to small farmers.…”
Section: Conclusion and Recommendationssupporting
confidence: 89%
“…A statistically significant correlation was found between farm size and keeping of financial information (both in terms of area and share total area). The findings support the studies carried out in other countries, as cited by Lalrinmawia and Gupta (2015), Sivakumar et al (2013), and Das and Maji (2023). As a result, more focus should be given to small farmers.…”
Section: Conclusion and Recommendationssupporting
confidence: 89%
“…Therefore, talking about financial education aims to create ecosystems with greater inclusion and participation (Heena and Himanshi, 2023). Das and Maji (2023) demonstrated that the determining factors for obtaining financial literacy include economic status, financial inclusion, marital status, and financial confidence.…”
Section: Theoretical Foundationmentioning
confidence: 99%
“…On the contrary, financial illiteracy is commonly associated with high-cost borrowing, inability to judge actual debt position and loan default (Lusardi and Tufano, 2015). Effective money management skills can reduce debt to income ratio and make individuals less prone to borrow from high-interest sources (Das and Maji, 2023).…”
Section: Financial Literacy and Financial Confidencementioning
confidence: 99%